Reduced Neutrophil Extracellular Trap (NET) Formation During Systemic Inflammation in Mice With Menkes Disease and Wilson Disease: Copper Requirement for NET Release - Cichon, Iwona; Ortmann, Weronika; Bednarz, Aleksandra; Lenartowicz, Malgorzata; Kolaczkowska, Elzbieta (Frontiers in Immunology, 2020)
Neutrophil extracellular traps (NETs) contribute to pathological disorders and their release was directly linked to numerous diseases. With intravital microscopy (IVM) we showed previously that NETs also contribute to the pathology of systemic inflammation and are strongly deposited in liver sinusoids. Over a decade since NET discovery still not much is known about metabolic or microenvironmental aspects of their formation. Copper is a vital trace element essential for many biological processes, albeit its excess is potentially cytotoxic, thus copper levels are tightly controlled by factors such as copper transporting ATPases, ATP7A and ATP7B. By employing IVM, we studied the impact of copper on NET formation during endotoxemia in liver vasculature on two mice models of copper excess or deficiency, Wilson (ATP7B mutants) and Menkes (ATP7A mutants) diseases, respectively. Here we show that respective ATP7 mutations lead to diminished NET release during systemic inflammation despite unaltered intrinsic capacity of neutrophils to cast NETs as tested ex vivo. In Menkes disease mice the in vivo effect is mostly due to diminished neutrophil infiltration of the liver as unmutated mice with a subchronic copper deficiency release even more NETs than their controls during endotoxemia. Whereas in Wilson disease mice excess copper directly diminishes the capacity to release NETs and this was further confirmed by ex vivo studies on isolated neutrophils co-cultured with exogenous copper and a copper chelating agent. Taken together, the study extends our understanding on how microenvironmental factors affect NET release by showing that copper is not a prerequisite for NET release but its excess affects the trap casting by neutrophils.